Into Tibet: An Early Pliocene Dispersal of Fossil Zokor (Rodentia: Spalacidae) from Mongolian Plateau to the Hinterland of Tibetan Plateau. - Qiang Li; Xiaoming Wang (PLoS ONE)
This paper reports the fossil zokors (Myospalacinae) collected from the lower Pliocene (~4.4 Ma) of Zanda Basin, southwestern Tibet, which is the first record in the hinterland of Tibetan Plateau within the Himalayan Range. Materials include 29 isolated molars belonging to Prosiphneus eriksoni (Schlosser, 1924) by having characters including large size, highly fused roots, upper molars of orthomegodont type, m1 anterior cap small and centrally located, and first pair of m1 reentrants on opposing sides, high crowns, and high value of dentine tract parameters. Based on the cladistics analysis, all seven species of Prosiphneus and P. eriksoni of Zanda form a monophyletic clade. P. eriksoni from Zanda, on the other hand, is nearly the terminal taxon of this clade. The appearance of P. eriksoni in Zanda represents a significant dispersal in the early Pliocene from its center of origin in north China and Mongolian Plateau, possibly via the Hol Xil-Qiangtang hinterland in northern Tibet. The fast evolving zokors are highly adapted to open terrains at a time when regional climates had become increasingly drier in the desert zones north of Tibetan Plateau during the late Miocene to Pliocene. The occurrence of this zokor in Tibet thus suggests a rather open steppe environment. Based on fossils of large mammals, we have formulated an "out of Tibet" hypothesis that suggests earlier and more primitive large mammals from the Pliocene of Tibet giving rise to the Ice Age megafauna. However, fossil records for large mammals are still too poor to evaluate whether they have evolved from lineages endemic to the Tibetan Plateau or were immigrants from outside. The superior record of small mammals is in a better position to address this question. With relatively dense age intervals and numerous localities in much of northern Asia, fossil zokors provide the first example of an "into Tibet" scenario--earlier and more primitive taxa originated from outside of the Tibetan Plateau and the later the lineage became extinct in southwestern Tibet.